How Prepared Are We for Possible Bioterrorist Attacks: An Approach from Emergency Medicine Perspective - Ali Kemal Erenler; Murat Güzel; Ahmet Baydin (The Scientific World Journal)
Preparedness for bioterrorist attacks and early recognition of specific agents are essential for public health. Emergency departments may play an important role in this field. The large spectrum of bioterrorism involves not only disastrous terrorism with mass casualties, but also microevents using low technology but producing civil unrest, disruption, disease, disabilities, and death. It aims not only to cause mortality and morbidity, but also to lead to social and political disruption. Preparedness appears to be the most potent defense against possible bioterrorist events. In this article, we aim to create awareness against biological agents and underline the importance of emergency departments in this public health problem.